Intention to drink alcohol among rural natives of Sarawak: an application of the theory of planned behavior - Rubiah Anak Ajan,; Yew, Wong Chin; Abd Hair Awang, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of alcoholic beverages is increasing worldwide, and it is the reason for the increase in mortality as well as health consequences. The rare explorations on alcohol consumption (AC) among Sarawak Natives indicated that risky drinking among the target ethnicities is higher compared to that of other ethnic groups. This study aims to identify the predictors of alcohol consumption (AC) among Sarawak Natives. The theory of planned behavior (TPB) was applied in this study to predict the intention to drink among the rural adult community in Malaysia. A crosssectional study was conducted among rural natives of Sarawak. The sample of this study consists of 293 rural adult communities who completed an adapted and reliable survey questionnaire assessing the constructs of TPB. Study factors such as attitudes (ATT), subjective norms (SNs), and perceived behavioral control (PBC) were proximal in predicting the intention to drink alcohol. Using the path analysis, the strongest proximal predictor of intention was ATT. The results of this study revealed that study factors namely ATT, SNs, and PBC have a direct and significant effect on the intention to drink among Malaysian rural adults. Therefore, policymakers have to launch an awareness campaign to increase the knowledge about the risk of drinking alcoholic beverages and enlighten people about the danger and health problems they might face if they continue to drink alcohol.